Trophic resources of the edaphic microarthropods: A worldwide review of the empirical evidence - Velazco, Víctor Nicolás (2023)
Fil: Velazco, Víctor Nicolás. Universidad Nacional de Luján. Departamento de Ciencias Básicas; Argentina.